Analysis of The Implementation of Nosocomial Infection Prevention and Control in Hospitals (A Literature Study) - Amira Mhuthia Adila; Nur Ramadhan; Puspa Nujulla; Putri Dwi Ardiyanti; Rina Oktavia; Shelly Fadhilah Muqsith; Vania Alda Nabilah; Zalma Nur Khadijah Putri; Munaya Fauziah (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Infections due to health services or Healthcare-Associated Infection (HAI) or known as nosocomial infections are infections that occur in patients during treatment in hospitals or other health facilities. The prevention and control of nosocomial infections is a worldwide challenge. This study aims to examine the literature, articles, or journals of research results regarding the implementation of prevention and control of nosocomial infections in hospitals. The method used is a literature review with 10 journals that were reviewed and written from 2015 to 2020, or written in the last 6 years with the keywords "Analysis of the Implementation of Nosocomial Infection Prevention and Control". The results obtained are 8 journals that have obstacles such as lack of Human Resources (HR), insufficient funds and infrastructure, there are still many officers who have not taken action according to Standard Operating Procedures (SOP), many officers have not received training, there is no incentive for officers. , there is an unbalanced workload, the reporting system is not maximized, the use of Personal Protective Equipment (PPE) is not optimal, and cough etiquette has not been carried out by officers. So it is necessary to add things that must be met such as training of officers, completing the needs (facilities and infrastructure) for officers, providing sanctions for officers when violating (not taking actions according to SOPs), providing incentives for officers, and even giving rewards for officers who obey comply SOP, especially given strict supervision from the hospital so that officers and patients do not transmit their disease to each other or other people.